2019
DOI: 10.1080/21691401.2019.1621886
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Astragalus polysaccharide alleviates H 2 O 2 -triggered oxidative injury in human umbilical vein endothelial cells via promoting KLF2

Abstract: The damage of vascular endothelial cells has become an indispensable factor in the occurrence and advancement of cardiovascular diseases. In the current study, we investigated the effect of Astragalus Polysacharin (APS) on H 2 O 2-evoked oxidative injury in HUVECs. HUVECs cells were treated by H 2 O 2 to induce oxidative damage. Cells viability, apoptosis and reactive oxygen species (ROS) level were detected through CCK8 assay and flow cytometry. The cell growth-related proteins and heme oxygenase-1(HO-1) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Astragalus polysaccharide (ASTP) reduces ROS generation and the expression of Baz, Caspase-9 and Caspase-3, increases HO-1 and Nrf2 expression, inhibits cell apoptosis, and effectively protects HUVECs from H 2 O 2 stimulation. KLF2, a transcription regulatory protein, primes Nrf2 for activation in endothelial cells, and the authors also found that ASTP can increase KLF2 expression [80] . Similarly, polysaccharides from Athyrium multidentatum (AMP) increase the survival rate of H 2 O 2 -damaged HUVECs, reduce ROS production, and enhance SOD and CAT activity.…”
Section: Protective Effects Of Herbal Medicine and Its Monomers On Vascular Endothelial Cells Related To Nrf2/ho-1mentioning
confidence: 89%
“…Astragalus polysaccharide (ASTP) reduces ROS generation and the expression of Baz, Caspase-9 and Caspase-3, increases HO-1 and Nrf2 expression, inhibits cell apoptosis, and effectively protects HUVECs from H 2 O 2 stimulation. KLF2, a transcription regulatory protein, primes Nrf2 for activation in endothelial cells, and the authors also found that ASTP can increase KLF2 expression [80] . Similarly, polysaccharides from Athyrium multidentatum (AMP) increase the survival rate of H 2 O 2 -damaged HUVECs, reduce ROS production, and enhance SOD and CAT activity.…”
Section: Protective Effects Of Herbal Medicine and Its Monomers On Vascular Endothelial Cells Related To Nrf2/ho-1mentioning
confidence: 89%
“…For instance, APS protects human umbilical vein endothelial cells from oxidative damage triggered by H 2 O 2 through promoting the expression of KLF2, thereby reducing the advancement of cardiovascular diseases (Li et al. 2019 ). APS also has antitumor effects in various cancers.…”
Section: Discussionmentioning
confidence: 99%
“… 2013 ; Li et al. 2019 ). Therefore, this study hypothesized that APS partakes in polarization of TAMs in HCC in order to inhibit HCC-like phenotypes including cell proliferation, migration and invasion.…”
Section: Introductionmentioning
confidence: 99%
“…Through the addition of inhibitors, it is found that all of the MAPKs are the key to regulation. The three pathways of JNK [ 1 ], MEK/ERK [ 31 ], and p38 [ 32 ] are regulated by regulating GPx, CAT, and SOD-2 in cells to protect the regulation of Bcl-2 and Bax on the mitochondrial membrane. PKE was found to promote cell proliferation in the MTT test, and it was confirmed in the results of the cell morphology observation and cell apoptosis analysis.…”
Section: Discussionmentioning
confidence: 99%